Hepatitis C virus non-structural 3/4A protein interferes with intrahepatic interferon-γ production. Issue 4 (3rd August 2011) - Brenndörfer, Erwin Daniel; Brass, Anette; Söderholm, Jonas; Frelin, Lars; Aleman, Soo; Bode, Johannes Georg; Sällberg, Matti
Abstract : Background: The non-structural (NS) 3/4A protease/helicase of the hepatitis C virus is known to modulate signalling pathways in the infected hepatocyte by cleaving CARD adaptor inducing IFNβ (Cardif), T-cell protein tyrosine phosphatase (TC-PTP) and TIR domain-containing adaptor inducing IFNβ (TRIF), but the effects of NS3/4A in vivo still remain unclear. Aim: To investigate the influence of NS3/4A on intracellular and intercellular signalling in vivo by analysing the intrahepatic inflammatory response of naïve, lipopolysaccharide (LPS)/d -galactosamine (d -galN) or tumour necrosis factor-α (TNFα)/d -galN-treated NS3/4A-transgenic (Tg) mice. Methods: The intrahepatic immunity of naïve and LPS/d -galN- or TNFα/d -galN-treated NS3/4A-Tg mice was determined using western blot, ELISA, real-time PCR, flow cytometry and survival monitoring. The injection of cytokines or antibodies against signalling components was performed to analyse the relevance of the respective pathways for the investigated issues. A Tg mouse lineage expressing an inactivated NS3/4A protease (NS3/4A Ile1073Ala -Tgs) was generated to examine if protective effects were NS3/4A protease dependent. Results: The activation of hepatic signal transducer and activator of transcription 1 and 2 was impaired in NS3/4A-Tg mice after treatment with LPS/d -galN or TNFα/d -galN. This was paralleled by a reduction in hepatic interferon-γ (IFNγ). Reconstitution of IFNγ reverted the resistance to LPS/TNFα in NS3/4A-Tg mice. Subsequently, blocking IFNγ in vivo rendered wild-type mice resistant against treatment with LPS/TNFα. A new Tg mouse expressing an inactivated NS3/4A protease had the same phenotype as wild-type mice with respect to hepatic IFNγ levels and sensitivity to LPS/d -galN. Finally, the chemokine profile was altered in the NS3/4A-Tg mice towards an anti-inflammatory state, which helps to explain the altered immune cell subsets and reduction in hepatic IFNγ production. Conclusions: Our data demonstrate that the NS3/4A protease reduces the intrahepatic production of IFNγ and alters TNFα-mediated effects, thereby impairing the hepatic inflammatory response. This may contribute to viral persistence.